MYXOCHLAMYS AMPHILOXA (ZINGIBERACEAE): A NEW SPECIES FROM CENTRAL KALIMANTAN, INDONESIA - Searle, R. J.; Newman, M. F. (Edinburgh Journal of Botany, 2010)
Myxochlamys amphiloxa R.J.Searle (Zingiberaceae) from Central Kalimantan Province, Indonesia is described and illustrated. An IUCN conservation assessment is made.